In Vitro Differentiation of Preosteoblast-Like Cells, MC3T3-E1, to Adipocytes Is Enhanced by 1,25(OH)2 Vitamin D3 - Pendleton, Elisha; Chandar, Nalini (Frontiers in Endocrinology, 2017)
Osteoblasts and adipocytes originate from common mesenchymal progenitor cells and are controlled by specific transcription factors. While 1, 25 dihydroxyvitamin D3 (Vitamin D) is known to be an important factor for osteoblast differentiation, there are conflicting reports regarding its effect on adipogenesis. In this study, we attempted to understand the effect of exposure of preosteoblasts (MC3T3-E1) to adipogenic media with and without Vitamin D and determined the expression of adipogenic genes during this process. Our studies show that while transdifferentiation of preosteoblasts occurred on exposure to adipogenic media, the effect of Vitamin D treatment was synergistic resulting in several hundred fold increase in adipocyte transcription factors C/EBPα and PPARγ (P<0.001)along with an increase in markers of adipogenesis and accumulation of lipid droplets in cells. Vitamin D treatment was also accompanied by 100-700 fold increases in Vitamin D receptor expression during the treatment period (P<0.001). In order to determine how the effect of vitamin D might compare to other genetic manipulations that promote adipogenic differentiation we stably knocked down retinoblastoma expression in MC3T3- E1 cells. Recent studies have suggested retinoblastoma (Rb1) tumor suppressor gene function to be critical to maintain osteoblasts function and inhibit adipocyte differentiation. We exposed MC3T3-E1 cells with reduced Rb1 expression to adipogenic media and found an increase in adipogenic differentiation when compared to cells with a full complement of Rb dosage. However the extent of the change was not as dramatic as seen with Vitamin D. These studies show that preosteoblasts are sensitive and respond to these manipulations that favor the adipocytic phenotype. While vitamin D is not known to directly affect targets in adipogenesis, our observations may have resulted from the malleability of preosteoblast genome in MC3T3-E1 cells, which allowed adipocyte specific gene expression under appropriate stimuli. Why this pathway is influenced and subverted by an anabolic bone factor such as vitamin D remains to be determined.